Case Report: A case of melanosis coli complicated by pneumatosis intestinalis–induced volvulus - Bai, Shuxia; Wang, Jiangbo; Song, Tingting; Sun, Wenjia (Frontiers in Medicine, 2025)
Melanosis coli (MC) combined with pneumatosis intestinalis (PI) is an exceedingly rare condition. We present the case of an 85-year-old male with a history of chronic constipation, hypertensive heart disease, and type 2 diabetes mellitus. The patient was admitted to the hospital because of an acute sigmoid volvulus with complete intestinal obstruction. After 3 days of conservative treatment, surgical intervention was performed, consisting of sigmoidectomy with volvulus reduction and formation of a descending colostomy. Histopathological examination confirmed MC with PI and associated mucosal necrosis. The patient, unfortunately, developed severe complications and eventually died of hemorrhagic shock and circulatory failure 22 days after surgery. This case explores the potential mechanisms underlying MC complicated by PI, emphasizing the need for increased clinical vigilance in elderly diabetic patients with chronic constipation and pre-existing cardiovascular disease, particularly following the use of anthraquinone-based laxatives and alpha-glucosidase inhibitors (αGIs).